Notes to the Tax System of Public Works of Infrastructure and Public Services Concessions - Tuesta Madueño, Arturo (2014)
In this report, the main Income Tax aspects related to the concessions of public infrastructure and of public services regulated by Supreme Decrete N° 059-96-PCM are analyzed. Hence, the applicable rules for investments made by the concessionaires and the treatment of self- sustained and co-financed concessions will be examined. To conclude this report, legislative changes that, in opinion of the authors would help provide greater security to the current regime on benefit of the Peruvian State and the investors, are suggested.